Cosuppression of latent and nominal allotypes in individual rabbit lymphocytes. - Wolf, B (1985)
Endogenous synthesis of latent and nominal allotype was observed in vitro in rabbit peripheral blood lymphocytes (PBL). PBL from rabbits displaying the nominal b4 specificity, as well as the latent b5 and b6 either on the cell surface or in the serum or both, were treated with pronase to remove surface latent and nominal allotypes and cultured in serum-free medium to regenerate the nominal and latent markers. Rosette formation using the mixed anti-globulin assay demonstrated that the nominal b4 and latent b5 and b6 specificities were displayed in the same cell. Cells were seen bearing the b4 + b5, b4 + b6, or b4 + b5 + b6, as double or triple expressors. No latent allotype-bearing cells were detectable in the absence of the nominal allotype. In vitro suppression of nominal surface b4 with anti-b4 antibodies resulted in the cosuppression of the latent b5 and b6. In contrast, in vitro suppression of latent b5 and b6 with anti-b5 and anti-b6 antibodies, respectively, did not cause the cosuppression of the nominal b4 allotype. Cosuppression of latent and nominal markers in the same cell confirms that the biosynthetic machinery for latent and nominal allotypes lies within the same cell.